1981
DOI: 10.1073/pnas.78.9.5386
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive DNA sequences cotranscribed with developmentally regulated Dictyostelium discoideum mRNAs.

Abstract: We have isolated a clone of Dictyostelium discoileum genomic DNA, pB41-6, that contains sequences that are reiterated and interspersed in the genome. The expression of these reiterated sequences is developmentally regulated, and they appear to be linked only to developmentally regulated mRNAs. We have used clone pB41-6 to isolate a set of complementary cDNA clones. Analysis of two selected clones indicates that they encode developmentally regulated mRNA species and, by means of the repetitive elements they con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

1982
1982
1985
1985

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…In Further complications may arise from repeat sequences in different mRNAs. These have been shown to exist in slime molds (18,41) and possibly affect the selection procedures (22). Our selection procedures included higher criteri- Quantitative measurements of the steadystate concentrations showed that individual pluteus-specific mRNAs accumulated to different extents.…”
Section: Discussionmentioning
confidence: 99%
“…In Further complications may arise from repeat sequences in different mRNAs. These have been shown to exist in slime molds (18,41) and possibly affect the selection procedures (22). Our selection procedures included higher criteri- Quantitative measurements of the steadystate concentrations showed that individual pluteus-specific mRNAs accumulated to different extents.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription of DIRS-1-related sequences results in the production of a heterogeneous population of polyadenylated cytoplasmic RNAs that are differentially expressed during development (7,24; C. Zuker, Ph.D. thesis, Massachusetts Institute of Technology, Cambridge). DIRS-1 RNAs are present at very low levels in growing cells, begin to accumulate within the first hour after initiation of development, and reach their maximal level by 15 h. Transcription of DIRS-1-related RNAs is induced in vegetative cells subjected to stresses such as heat shock and high cell density (22).…”
mentioning
confidence: 99%
“…Dictyostelium discoideum AX-3 was grown axenically and plated for development on filters as described previously (1). Growing cells were harvested when the concentration reached 2 x 106 cells per ml.The DIRS-1 genomic clones used here (pB41.6 and pB41.3) are subclones of the A genomic clone SB41 and have been described in detail elsewhere (7,22,24 …”
mentioning
confidence: 99%
See 2 more Smart Citations